The effect of maternal serum lipid on maternal blood pressure and fetal birth weight. A prospective Cohort Study at maternal child health centre - Nusee, Zalina; Ho, Kah Seong; Abdullah, Suhaiza; Ismail, Hamizah (2014)
Objective: To assess the social-demographic characteristic and the maternal risk factors for pre eclampsia (PE) especially maternal fasting serum lipids (FSL) between trimesters. It was also to find out the association between FSL with fetal birth weight at a primary maternal child health center (KKIA). Materials and methods: A prospective cohort study was designed for recruiting pregnant women who were in their 1st trimester at KKIA at Jalan Gambut Kuantan Pahang. The study involved taking fasting serum lipids (FSL), blood pressure (BP) measuring and urine albumin in every trimester. The data was analyzed using (SPSS) version 17.0 and p value of < 0.05 was considered as statistically significant.